AN ANALYSIS OF RELATIVE CLAUSES MADE BY THE EIGHT GRADE STUDENTS OF SMP NEGERI 3 SELAT IN ACADEMIC YEAR 2017/2018 - Ni Made Lisma Martarini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The present study is dealt with An Analysis of Relative Clauses Made by theEight Grade Students of SMP Negeri 3 Selat in Academic Year 2017/2018. Theresearcher was interested in making an analysis of Relative clauses made by thestudents under study. The present study is intended to assess the acquisition ofrelative clauses made by the eighth-grade students of SMP N 3 Selat Karangasemin academic year 2017/2018. In other words, this study is to figure out the ability ofthe subject under study in understanding relative clauses. The present’s studywhich use ex-post facto research design with descriptive analysis was intended toanswer the following research question: to what extent is the acquisition of relativeclauses made by the eighth-grade students of SMP N 3 Selat Karangasem inacademic year 2017/2019? In order to answer the research question before, the datawere required for the present study which in the form of raw score is showing theability of the students in mastering relative clauses, were collected by administeringthe valid and reliable research instrument in form of multiple-choice test items.Then the data is analyzed by using Norm-Reference measure with five standardvalues. The populations of the present study are the eighth-grade students of SMPNegeri 3 Selat which consist of 206 students. They are considered to haveheterogeneous characteristics. In this study 30 students are considered as a sampleof the study by using random sampling technique. The data of the study is clearlyshowed that: (1) there are 4 students or (13.33%) out of 30 students under study whoshowed excellent ability of relative clauses. (2) There are 4 students or (13.33%) outof 30 students under study who showed good ability of relative clauses (3) there are10 students or (33.33%) out of 30 students under study who showed sufficientability of relative clauses. (4) There are 12 students or (40%) under 30 students understudy who showed insufficient ability of relative clause. (5) No one students or (0%)out of 30 students who showed poor ability of relative clauses. In the result of thestudy were used as the basses to assign level/grade to the subject under study, thereare 12 students or 40% out of 30 students under investigation who fail in learningand acquiring relative clauses. It means that 40% of them still have low ability. Thefinding of the present study can be used as the basses in planning much betterlanguage teaching especially in mastering grammar or relative clauses.